Establishment and characterization of a buffalo (Bubalus bubalis) mammary epithelial cell line. - Vijay Anand (Public Library of Science (PLoS), 2012)
Background The objective of this study was to establish the buffalo mammary epithelial cell line (BuMEC) and characterize its mammary specific functions. Methodology Buffalo mammary tissue collected from the slaughter house was processed enzymatically to obtain a heterogenous population of cells containing both epithelial and fibroblasts cells. Epithelial cells were purified by selective trypsinization and were grown in a plastic substratum. The purified mammary epithelial cells (MECs) after several passages were characterized for mammary specific functions by immunocytochemistry, RT-PCR and western blot. Principal findings The established buffalo mammary epithelial cell line (BuMEC) exhibited epithelial cell characteristics by immunostaining positively with cytokeratin 18 and negatively with vimentin. The BuMEC maintained the characteristics of its functional differentiation by expression of β-casein, κ-casein, butyrophilin and lactoferrin. BuMEC had normal growth properties and maintained diploid chromosome number (2n = 50) before and after cryopreservation. A spontaneously immortalized buffalo mammary epithelial cell line was established after 20 passages and was continuously subcultured for more than 60 passages without senescence. Conclusions We have established a buffalo mammary epithelial cell line that can be used as a model system for studying mammary gland functions.